Rationality and Judgment - Siegel, Harvey (Metaphilosophy, 2004)
Philosophical/epistemic theories of rationality differ over the role of judgment in rational argumentation. According to the "classical model" of rationality, rational justification is a matter of conformity with explicit rules or principles. Critics of the classical model, such as Harold Brown and Trudy Govier, argue that the model is subject to insuperable difficulties. They propose, instead, that rationality be understood, ultimately, in terms of judgment rather than rules. In this article I respond to Brown's and Govier's criticisms of the classical model, and to the "judgment model" they propose in its place. I argue that that model is unable both to distinguish between rational and irrational judgment and to avoid recourse to rules, and is therefore inadequate as an account of rationality, critical thinking, or argument appraisal. More positively, I argue that an adequate account of rationality must include a place for both rules and judgment.